2011
DOI: 10.1007/s13197-010-0225-8
|View full text |Cite
|
Sign up to set email alerts
|

Trans fats—sources, health risks and alternative approach - A review

Abstract: Trans fatty acids have the presence of one or more double bonds in the trans configuration instead of the usual cis configuration. They are desired by Vanaspati industry as they impart firmness to margarines and plasticity as well as emulsion stability to shortenings. Research has proved the direct connection of trans fatty acids with cardiovascular diseases, breast cancer, shortening of pregnancy period, risks of preeclampsia, disorders of nervous system and vision in infants, colon cancer, diabetes, obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(174 citation statements)
references
References 40 publications
(38 reference statements)
2
150
0
2
Order By: Relevance
“…Milk fat is composed of saturated fats and cholesterol to complicate the matters for health-conscious consumers and people suffering from coronary heart diseases and/or diabetes (Patel et al 2010). Many epidomiological studies have shown a positive correlation between total cholesterol (TC) level, especially low density lipoprotein (LDL) cholesterol level and cardiovascular heart disease (CHD) (Ney 1991;Dhaka et al 2011). The level of TC and LDL cholesterol in blood serum is affected by the consumption of fatty foods in the diet (Ney 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Milk fat is composed of saturated fats and cholesterol to complicate the matters for health-conscious consumers and people suffering from coronary heart diseases and/or diabetes (Patel et al 2010). Many epidomiological studies have shown a positive correlation between total cholesterol (TC) level, especially low density lipoprotein (LDL) cholesterol level and cardiovascular heart disease (CHD) (Ney 1991;Dhaka et al 2011). The level of TC and LDL cholesterol in blood serum is affected by the consumption of fatty foods in the diet (Ney 1991).…”
Section: Introductionmentioning
confidence: 99%
“…TFA is one of the main saturated byproducts of vegetable oils, which is produced by industrial processes (11). These fatty acids (especially elaidic acid or EA C18:1.9) cause the development and progression of atherosclerosis through change in the lipid profile, exacerbation of inflammation, inflammatory factors, and other major complications (12).…”
Section: Vol1 No1 Spring 2017mentioning
confidence: 99%
“…4 , with a small amount of linolenic acid 6.2 , palmitic acid 1.4 , and stearic acid 1.1 . However, the FA moiety at sn-2 position of the produced SLs was found to be significantly changed after the catalytic interesterification reaction.…”
Section: Catalytic Activity Of the Solid Catalystmentioning
confidence: 99%